Social Closure and Disparity in Vietnam: A Bourdieuian Analysis - Nguyen, Lisa; Hooper, Keith; Sinclair, Rowena (Asian Journal of Business and Accounting, 2012)
The purpose of this paper is to examine historically the practice of social closure and the resulting disparity in the accounting profession in Vietnam. Although such social closure may exist in other emerging economies, there are external influences peculiar to each economy which exacerbates such disparities. This research applies Bourdieu’s theories to explain social closure and the disparities between bookkeepers and professional accountants. The historical development of the Vietnamese accounting profession is also examined, to trace the origins of these disparities. Social closure - with its origins in French concepts of professional closure - is cited as the main reason for such a disparity between bookkeepers and professional accountants. This research adopts a conceptual, historical approach to explain social closure and examines how the professions were conceived and how the colonial experience left its legacy in the structure of the accounting profession in Vietnam. Keywords: Accounting Profession, Bookkeepers, Professional Accountants, Social Closure, Vietnam